Quarter Life Crisis “Aku Ga Bisa Yura”: Studi Fenomenologi pada Mahasiswa di Kota Semarang - Jajim Fuadi; Dhwiya Sekar Kinasih; Nadia Amilatur R; Nandita Novia A; Ashari Mahfud; Muslika Muslika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research aims to examine the phenomenon of quarter life crisis among university students in Semarang City, which was triggered by the TikTok trend “Aku Ga Bisa Yura.” The scope of this paper includes an analysis of the five phases of quarter life crisis, starting from the feeling of being trapped, the desire to change the situation, to the crucial actions taken, as well as how individuals build a life according to their values and interests. The method used is a phenomenological study with in-depth interview techniques with five subjects representing various experiences and problems related to quarter life crisis. The results of the discussion show that students feel the complexity of facing the transition to adulthood, and although faced with uncertainty, they are able to take positive steps to achieve life goals that are more in line with themselves. The conclusion of this study confirms that quarter life crisis, although challenging, can be a process that results in significant personal development, and points to the need for further understanding of the influence of social media in shaping students' perceptions of this crisis. This research also suggests conducting a broader study involving students from different regions and other social media platforms.